Development and implementation of a mathematical model for environmental impact of seawater intrusion evaluation in the Capline river aquifer, Tacna, Perú. - Rojas Gonzáles, E. (2010)
The over-exploitation of our country’s coastal aquifer to supply water demand for domestic and agricultural use has caused in recent years an increasing problem of seawater intrusion into these aquifers. One way for diagnosis and solutions design to solve this problem came from the mathematical modelling of the transitional regime, which basically consist in the numerical solution of the dynamical equations of water flows in a aquifer by finite difference techniques. The area of application of the model developed was the Caplina aquifer in Tacna, Peru. The monthly calibration stage, the model achieved reproduce the behavior of the aquifer for the year 2000 with 95% of approximation, it means a 5% error between the historical piezometry and the piezometry obtained for the developed model. Considering the future growth of the developed model, which give a new position of the interface freshwater-seawater. By simulating the scenario-1, the results indicate that not represent a danger to the coastal area of the Caplina valley while the simulation of the scenario-2, the results indicate that the aquifers water reserves is endangered.